Diseño de un plan de negocios para la creación de un restaurante de comida típica ecuatoriana en la ciudad de Quevedo provincia de Los Ríos en el año 2013 - Guaranda Herrera, Paola Elizabeth (2013)
SUMMARY RECUTIVO The proposal of this plan, is to design a restaurant looking out from the crowd in the city of Quevedo, thank caraacterísticas as service quality and of course that will be offered food, dishes prepared with ingredients from Ecuador and organic and fresh spices produced in the regions of our country, which we guarantee a cominda healthy, nutritious and as if estubieramos tasting in our own home. Results from the data collection instruments implemented in the study showed that the restaurant features proposed in this work if they are valued by potential consumers. This indicates that if there is a market opportunity. This despite the fact that today in the historic commercial district aperturados are functioning normally and no less than 20 restaurants, 8 Chifas, 15 mobile food carts and KFC fast-food restaurant, which is the main copetencia for gourmet shops within the urban area of the city. We must also mention that to the north we find the Paseo Shopping Mall, within which there is a varied food court. One goal is to make the restaurant is among the most recognized of Quevedo, generating high levels of benefits and profits and employment opportunity is for many people. In short, the typical Ecuadorian food restaurant is a good proposal will enter astronomical Quevedo, creating quality jobs and paid for about 12 people initially. The typical Ecuadorian food restaurant is expected to become an alternative then completely different from the other restaurants in town and enthrall each and every one of your customers, not only because of their exceptional service, but by the quality of its food